The hyperfine field of selenium in iron and the magnetic dipole moment of Se-75 - Stone, N; Ohya, S; Ohtsubo, T; Muto, S; Nishimura, K (2001)
New results on the applied field dependence of the NMR of Se-75 implanted in pure iron and oriented at millikelvin temperatures are reported. They yield the magnetic hyperfine field acting on Se nuclei present as dilute impurities in the iron matrix and the magnetic dipole moment of the 5/2(+) ground state of Se-75 with significantly improved precision. The results are B-hf(SeFe) = +67.9(10) T and μ\(Se-75) = 0.683(10) mu (N). The improved value of the hyperfine field, with data from [2], gives the magnetic dipole moment of the 9/2(+) ground state of Se-73 as μ\ = 0.892(13) mu (N).